The experience of self-management, exercise and cultural belief among older adults living with knee osteoarthritis: a qualitative study - Abdul Hamid, Siti Hazariah; Nurumal, Mohd. Said; Che Hasan, Muhammad Kamil; Abidin, Muhammad Faiz; Arifin, Hidayat; Tan, Maw Pin (Universiti Putra Malaysia, 2025)
Introduction: Knee osteoarthritis (OA) affects about 3.8% of the global population, with higher prevalence among older adults: around 10% of men and 13% of women aged 60 and above. Those with knee OA often endure chronic pain, movement difficulties, and reduced ability to perform daily tasks. Understanding how individuals manage knee OA is essential to uncovering their actual practices and improving care. This study aimed at exploring the experience of older adults living with knee osteoarthritis within the context of cultural influence in Malaysia setting. Methods: A generic qualitative study was conducted using purposive sampling among older adults living with knee osteoarthritis attending two local hospitals in Kuantan, Pahang, Malaysia. Fifteen semi-structured interviews, ranging from 40 to 90 minutes each were conducted from September 2021 until January 2022. The data were transcribed and analysed using thematic analysis. Results: The findings are organised around three major themes: living with knee pain (impact on daily living activities; impact on religious practice), self-management (seeking treatment from health facilities; exercise with knee osteoarthritis; complementary therapies; dietary and food intake; coping mechanisms), and the impact of local cultural and religious beliefs (religious belief; cultural practice). Conclusion: Attention to the role of self-management and exercise activity embedded in daily lives should be applied to promote better well-being, particularly when dealing with culturally sensitive older adults living with knee osteoarthritis in Malaysia. Nurses can help older adults by providing education about disease management, assisting with activities of daily living, culturally competence and promoting socialisation based on the context of population.